Database Performance Management in Cloud - Navendu Mishra; Jayant Sawarkar; Suraj Dubey (International Journal of Engineering and Management Research, 2020)
Managing large chain of Hotels and ERP database comprises of core areas such as HRMS & PIP.HRMS (Human Resource Management System), which further includes areas such as Soft Joining, Promotion, Transfer, Confirmation, Leave Attendance and Exit, etc. PIP (Payroll Information Portal), wherein employees can view their individual Salary details, submit investment declaration, Reimbursement claim & CTC structuring, etc. Management of Large Chain of Hotels and ERP Database in AWS Cloud involves continuous monitoring with regards to the areas such as Performance of resource usages and optimization techniques relating to the use of PL/SQL. High Availability (HA) of data is accomplished through the Backup and Recovery mechanism and security of the data by Encryption & Decryption mechanism.